Serotype 3 as a challenging phenotype in pneumococcal early-onset sepsis: case report and 25-year literature review - Abiel Homero Mascareñas De Los Santos; Melissa Esmeralda Martínez Morán; Paul Santiago Arcos Viscarra; José Iván Castillo Bejarano; Denisse Natalie Vaquera Aparicio (BMC Pediatrics, 2026)
Abstract Background Neonatal early-onset sepsis (EOS) caused by Streptococcus pneumoniae is a rare but life-threatening, presenting with a fulminant clinical course despite vaccine-driven epidemiological shifts in older populations. Serotype 3 is notorious for its thick polysaccharide capsule and high virulence, yet its specific neonatal phenotype remains poorly characterized. We present a case of severe serotype 3 EOS integrated with a 25-year systematic literature review to elucidate the clinical pattern of this phenotype, differentiating the role of intrinsic virulence from antimicrobial resistance. Case presentation A term female neonate developed severe respiratory distress, metabolic acidosis, and multilineage cytopenias on her first day of life. Chest radiography revealed a reticulonodular pattern consistent with neonatal pneumonia. Blood cultures rapidly isolated S. pneumoniae , later identified as capsular serotype 3, which was fully susceptible to penicillin. The patient was successfully managed with targeted intravenous ampicillin, achieving rapid and complete clinical recovery. Results To contextualize this presentation, a 25-year literature review identified 41 confirmed cases of pneumococcal EOS. Overall, symptom onset was hyper-acute, with 63.4% ( n = 26/41) of the cohort becoming symptomatic within the first 24 h of life. Among the 34 serotyped isolates, serotype 3 was the most prevalent (26.5%, n = 9/34). Serotype 3 infections were associated with an atypical clinical behavior and a higher mortality rate compared to non-serotype 3 cases (33.3% vs. 16%, p = 0.33). Remarkably, 88.8% of these serotype 3 isolates, including the index case, retained full susceptibility to penicillin. Conclusions S. pneumoniae serotype 3 may point to a challenging clinical profile in neonatal EOS, characterized by early and acute onset of respiratory failure, widespread systemic involvement, and a trend toward higher mortality within this cohort. This occurs despite preserved susceptibility to beta-lactam antibiotics, suggesting a potential interplay between capsular features and host vulnerability rather than antimicrobial resistance. Thus, the persistence of this vaccine-included serotype highlights the need for continued epidemiological surveillance.